STUDI TENTANG KOMPETENSI PROFESIONAL KEPALA MADRASAH ALIYAH NEGERI 1 SINJAI - Vita, Nur; Ardiansyah, Muhammad; Hasan (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study examines the professional competence of the Principal of Madrasah Aliyah Negeri 1 Sinjai. The research focuses on how the principal’s professional competence is implemented and the supporting and inhibiting factors that influence its realization. This study employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The research aims to describe the professional competence of the principal and identify the factors that support and hinder its implementation. Data sources include the principal, teachers, staff, and official school documents. The findings show that the principal’s professional competence is reflected through: (1) the development of a vision and learning culture demonstrated by religious activities, character-building routines, and literacy programs; (2) learner-centered instructional leadership, evident in supervision of planning, implementation, and evaluation of learning, teacher professional development, and student involvement in various activities; (3) effective and transparent resource management, shown through an open RKAM, BOS accountability reports, internal audits, and documented task distribution. Supporting factors include strong teacher and staff collaboration, involvement of the school committee and parents, and adequate facilities. Inhibiting factors include limited funding, suboptimal teacher participation, communication barriers, and a high administrative workload.